THE INFLUENCE OF SOCIAL MEDIA ON CAMEROONIAN ENGLISH - Alobwede, Charles Esambe (International Journal of Research -GRANTHAALAYAH, 2023)
Social media has emerged as a popular new technology that has spread all over the different sectors in Cameroon: education, business, government, print media, audiovisual media, etc. This new means of communication has eased the exchange of thoughts and ideas. The internet, as an aspect of new technologies, came along with a deviant form of writing peculiar to the younger generation in general and the Cameroonian youth in particular. This new system of communication gave rise to what is known as computer-mediated communication, which had become widely spread within the educational milieu in Cameroon. Social media has negatively influenced the use of Standard English in Cameroon, especially written texts, given that aspects of computer-mediated communication have rapidly replaced conversational writing forms. Such development in communication has affected language, which has gradually shifted from its original sound, sign, or symbol and complex sentence structures governed by grammatical rules to the language of text messaging with its simple syntax, incomplete sentence forms, informal structures, and modified ideograms known as emojis (happy faces, sad faces, excitement figures, blushing faces, etc.). This research aimed at analysing the writings of students at the University of Yaounde 1 to show the extent to which the use of social media has affected the written rendition of these students. To elucidate this, a study was done by analyzing their scripts and text messages. The communication accommodation theory was adopted to arrive at the expected results.